Interactions of the G quartet forming semaphorin 3F RNA with the RGG box domain of the fragile X protein family - Menon, Lakshmi (Oxford University Press, 2007)
Fragile X syndrome, the most common cause of inherited mental retardation, is caused by the transcriptional silencing of the fmr1 gene due to an unstable expansion of a CGG trinucleotide repeat and its subsequent hypermethylation in its 5′ UTR. This gene encodes for the fragile X mental retardation protein (FMRP), an RNA-binding protein that has been shown to use its RGG box domain to bind to G quartet-forming RNA. In this study, we performed a detailed analysis of the interactions between the FMRP RGG box domain and one of its proposed RNA targets, human semaphorin 3F (S3F) RNA by using biophysical methods such as fluorescence, UV and circular dichroism spectroscopy. We show that this RNA forms a G quartet-containing structure, which is recognized with high affinity and specificity by the FMRP RGG box. In addition, we analyzed the interactions of human S3F RNA with the RGG box and RG cluster of the two FMRP autosomal paralogs, the FXR1P and FXR2P. We found that this RNA is bound with high affinity and specificity only by the FXR1P RGG box, but not by the FXR2P RG cluster. Both FMRP and FXR1P RGG box are able to unwind the G quartet structure of S3F RNA, however, the peptide concentrations required in this process are very different: a ratio of 1:6 RNA:FMRP RGG box versus 1:2 RNA:FXR1P RGG box.